A NEW SPRAY DRYER SUPPORTED WITH FREELY ROTATABLE PROPELLERS ENABLES MORE EFFICIENT DRYING OF MILK SAMPLES - Isik, Sinem; Yildiz, Cengiz (Vinca Inst Nuclear Sci, 2022)
A new type of spray dryer was developed for drying milk and the like efficiently. To this end, freely rotatable propellers powered with air-flow were placed in the drying chamber to increase thermal efficiency and the product yield in the newly developed spray dryer. Milk samples were dried in both the developed system and a standard spray dryer to compare thermal efficiencies and product yields of each. It was observed that the propellers placed in the drying chamber of the developed spray dryer had caused a change in the flow direction of the drying air, decreased the temperature of the drying walls, and increased the thermal efficiency and product yield in drying. Consequently, in the developed dryer, the adhesion of the powder particles to the drying wall and to each other is significantly reduced, resulting in a more efficient drying.
Keywords: spray drying; milk powder; thermal efficiency; wall deposition; product yield; particle size